PENGARUH STATUS SOSIAL EKONOMI MAHASISWA TERHADAP PERILAKU PERGANTIAN MEREK (BRAND SWITCHING BEHAVIOR) PADA TELEPON SELULER - Desi Relga Budi Calestin; Bintang Wirawan (SOSIOLOGI: Jurnal Ilmiah Kajian Ilmu Sosial dan Budaya, 2018)
This research aims to find out and analyze the influence of socioeconomic status of students against the behavior of the turn of the brand on a mobile phone on a student majoring in Sciology, Faculty of social and political sciences of the University of Lampung. The approach used in this study was the quantitative approach, this approach in using primary research strategy survey using a questionnaire for the collection of data. Respondents in this study amounted to 68 people, the determination of the sample in this study using random sampling techniques. The analysis of the data used in this study uses regression and correlation analysis. The results showed: (1) many of the students who become the respondents do not have excess consumption patterns, or just something to consume goods or services which only they need, as well as the type and uses a cell phone. (2) there is the influence of social economic status among students with behavior turn brand on mobile phones, students are not affected by the prestige that are on cell phones but rather uses a cell phone. (3) based on the results of the analysis of the correlation, there is a significant relationship between socio-economic status of the elderly with the behavior of the turn of the brand on mobile phones and the results are on the level of correlation is weak. That is, the Although there is a significant relationship but relationship between socio-economic status of the elderly with the behavior of the turn of the brand on the Sociology student less closely.